O indivíduo e a organização: a relação entre valores, personalidade e tipos de cultura organizacional - Lima, Flavia Pires Barbosa (2010)
Organizational culture, as indicated by specialized literature, influences the formulation of strategies, organizational change processes, workers commitment and well-being, main factors for the attainment of organizational competitiveness. Some studies have showed the importance of personal characteristics for organizational culture, specially the founders values. However, studies analyzing the relations between managers basic values and those of other workers, as well as relations between their personal values related to work, personality and types of organizational cultures have not been found. The aim of this research is to identify the relations between basic values, personal values related to work, types of personality and types of organizational culture in order to contribute to organizational culture studies. The hypothesis tested was that basic values, personal values related to work and types of personality present opposition and compatibility relations to types of structures of each of the constructs involved.The research was carried out with a non-probabilistic sample of 315 participants from four companies of different areas. The data were collected from questionnaires on a website created to that purpose and were analyzed with multivariate and descriptive quantitative techniques. The results showed that basic values and types of personality presented compatibility and opposition relations with types of culture as expected, but this did not happen in the relation between personal values related to work and types of culture.